Magnetic tweezers to capture the fast-folding λ6-85 in slow motion - César Augusto Quintana-Cataño; Ann Mukhortava; Mordjane A. Boukhet; Andreas Hartmann; Karl-Ludwig Schumann; Michael Schlierf (Communications Physics)
Abstract Force spectroscopy gives access to the underlying free energy landscape of protein folding. Proteins exhibit folding rates between microseconds and hours. To access slow folding rates, magnetic tweezers have shown to be a promising tool, yet it remained unclear if magnetic tweezers capture kinetics of ultra-fast folding proteins. Here, we study the folding mechanics and kinetics of λ6-85; a five-helix bundle protein with fast ~20 µs folding time in the thermal denaturation midpoint. We observed two-state folding of λ6-85 at ~ 6.2 pN and ~ 250 ms folding time in the mechanical midpoint. With optical tweezers, we found that λ6-85 folds at the mechanical midpoint with ~ 15 ms, 16-fold faster than in magnetic tweezers. To resolve the discrepancy between magnetic and optical tweezers, we developed a physics-based model taking into account the constant force condition of magnetic tweezers and the spacer mechanics. Using this model, we reach agreement between magnetic tweezers, optical tweezers and thermal denaturation experiments. In summary, we show that magnetic tweezers capture kinetics of ultrafast conformational changes, even at low forces. The model for extrapolation of the kinetics to force-free conditions provides opportunities of comparability for the growing community of magnetic tweezers force spectroscopy.